Actin Assemblies in the Axon Shaft – some Open Questions. (August 2018) - Dubey, Pankaj; Jorgenson, Kent; Roy, Subhojit
Abstract : The actin cytoskeleton in neurons plays critical roles in axonal growth and synaptic organization. Until recently, most studies on axonal actin were limited to terminal growth cones or synapses, whereas the organization of actin along the shaft of the axon was relatively ignored. However, experiments using super-resolution microscopy and live imaging have revealed previously unknown actin structures along the axonal shaft, such as periodic 'actin rings' circumferentially wrapping underneath the plasma membrane and dynamic actin pools deeper within the axon shaft (termed actin 'hotspots' and 'trails'). In this short review, we highlight some open questions that have surfaced as a direct result of these discoveries.